Zap: Automated Theorem Proving for Software Analysis - Ball, Thomas; Lahiri, Shuvendu; Musuvathi, Madanlal; Ball, Thomas; Musuvathi, Madan (Springer Verlag, 2005)
Automated theorem provers (ATPs) are a key component that many software verification and program analysis tools rely on. However, the basic interface provided by ATPs (validity/satisfiability checking of formulas) has changed little over the years. We believe that program analysis clients would benefit greatly if theorem provers were to provide a richer set of operations. We describe our desiderata for such an interface to an ATP, the logics (theories) that an ATP for program analysis should support, and present how we have incorporated many of these ideas in Zap, an ATP built at Microsoft Research.
Logic for Programming, Artificial Intelligence, and Reasoning (LPAR '05)